2017
DOI: 10.15835/nsb9310061
|View full text |Cite
|
Sign up to set email alerts
|

Veterinarians’ Perception, Knowledge and Practices of Antibiotic Stewardship in Enugu State Southeast, Nigeria

Abstract: A cross-sectional survey utilizing structured questionnaires was used to study the veterinarians' perception, knowledge and practices of antibiotic stewardship (ABS) in Enugu State, Southeastern Nigeria. Data obtained were analyzed using chi-square on SPSS (Version 15.0) at a significance level of P < 0.05 to determine possible associations between variables and perceptions/knowledge about ABS. Out of 280 respondents, 41 (17.1%) had heard about ABS. Minority of the respondents perceived/knew that using antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 44 publications
3
30
1
Order By: Relevance
“…In Nigeria, a fresh VM graduate is expected to start prescribing drugs from inception of a compulsory one year national youth service, thus every Nigerian veterinarian is a potential prescriber and dispenser of AB (Fairles, 2013;Anyanwu and Kolade, 2017), and there are limited opportunities (if there is any) for postgraduate training in ABS, particularly outside the academic setting (Wasserman et al, 2017). Further, there is no residency (house job/internship) programme for fresh VM graduates, and veterinarians (most of which have no experience/skill on graduation) are allowed to start prescribing (with or without supervision by senior veterinarians) and dispensing AB immediately on graduation from veterinary schools (Anyanwu and Kolade, 2017). Given the importance of veterinarians as key partners in ABS efforts, VMS should therefore be knowledgeable about ABR and ABS (Brink et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In Nigeria, a fresh VM graduate is expected to start prescribing drugs from inception of a compulsory one year national youth service, thus every Nigerian veterinarian is a potential prescriber and dispenser of AB (Fairles, 2013;Anyanwu and Kolade, 2017), and there are limited opportunities (if there is any) for postgraduate training in ABS, particularly outside the academic setting (Wasserman et al, 2017). Further, there is no residency (house job/internship) programme for fresh VM graduates, and veterinarians (most of which have no experience/skill on graduation) are allowed to start prescribing (with or without supervision by senior veterinarians) and dispensing AB immediately on graduation from veterinary schools (Anyanwu and Kolade, 2017). Given the importance of veterinarians as key partners in ABS efforts, VMS should therefore be knowledgeable about ABR and ABS (Brink et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Ferdoush et al (2016) reported that 6% among 171 4th-year students in 3 Bangladeshi medical schools were familiar with the term AMS while less than two-third of 289 final-year students in 3 South African medical schools reported familiarity with the term ABS (Wasserman et al, 2017). Anyanwu and Kolade (2017) reported that 17.1% among 280 practicing/teaching veterinarians in Enugu State Nigeria have heard of ABS. The disparities in these studies may be due to differences in ABS awareness education that has been conducted in the various health profession institutions, degree of integration in the curricula and teaching of AMS education in the institutions, and/or the degree of AMS education awareness that has been conducted via sources such as mass media, journals, peers, etc in the study area (Lee et al, 2015;Anyanwu and Kolade, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations